Measurements of Atmospheric Water Vapor by a 1.316 μm Optical Fiber Laser Heterodyne Radiometer - Huang, Jun; Huang, Yinbo; Lu, Xingji; Liu, Dandan; Yuan, Zihao; Qi, Gang; Cao, Zhensong (Frontiers in Physics, 2022)
A passive optical fiber laser heterodyne radiometer prototype with a semiconductor laser near 1.316 μm as the local oscillation was built, parameters of the prototype have been optimized. Using the prototype, the water vapor concentration in the atmospheric column was measured with a spectral resolution of 0.009 cm-1 in late October and early November of 2020, the collection time was approximately 3 min, and the signal-to-noise ratio was better than 120. The water vapor column concentration and profiles were inversed based on the optimal estimation method. Compared with the measurement of the Fourier transform spectrometer (EM27/SUN) which was performed simultaneously, the inversion results deviated by less than 14%, and the variation trend of the water vapor concentration showed good consistency. It is demonstrated that the 1.316 μm optical fiber laser heterodyne radiometer possesses good stability and accuracy in the field measurement of atmospheric water vapor concentration.